2017
DOI: 10.4077/cjp.2017.baf469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B Vitamins Overload on Plasma Insulin Level and Hydrogen Peroxide Generation in Rats

Abstract: It has been reported that nicotinamide-overload induces oxidative stress associated with insulin resistance, the key feature of type 2 diabetes mellitus (T2DM). This study aimed to investigate the effects of B vitamins in T2DM. Glucose tolerance tests were carried out in adult Sprague-Dawley rats treated with or without cumulative doses of B vitamins. More specifically, insulin tolerance tests were also carried out in adult Sprague-Dawley rats treated with or without cumulative doses of Vitamin B3. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, the observed effects of RP and/or AA were more prominent with the modulation of up to 70% of OME-induced mutagenicity in A. cepa. There are reports that the association of vitamins has importance in the protection and inhibition of oxidative effects (Sun et al, 2017) and prevention of risks for several types of cancer, such as adenomas (Xu et al, 2013), colon (Heine-Bröring et al, 2015), ovary (Koushik et al, 2015, prostate (Tomasetti et al, 2012) and especially for gastric cancer (Kong et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the observed effects of RP and/or AA were more prominent with the modulation of up to 70% of OME-induced mutagenicity in A. cepa. There are reports that the association of vitamins has importance in the protection and inhibition of oxidative effects (Sun et al, 2017) and prevention of risks for several types of cancer, such as adenomas (Xu et al, 2013), colon (Heine-Bröring et al, 2015), ovary (Koushik et al, 2015, prostate (Tomasetti et al, 2012) and especially for gastric cancer (Kong et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This increases the likelihood that obesity and T2DM may be related to excessive intake of B vitamins. It has been reported that excess vitamins B6 metabolism significantly increases plasma H 2 O 2 levels [ 51 ]. The level of pyruvic acid is also higher in T2DM patients [ 52 ].…”
Section: Discussionmentioning
confidence: 99%